Glutathione S‐transferase omega‐2 polymorphism Asn142Asp modifies the risk of age‐related cataract in smokers and subjects exposed to ultraviolet irradiation. (24th September 2013) - Stamenkovic, Miroslav; Radic, Tanja; Stefanovic, Ivan; Coric, Vesna; Sencanic, Ivan; Pljesa‐Ercegovac, Marija; Matic, Marija; Jaksic, Vesna; Simic, Tatjana; Savic‐Radojevic, Ana
Abstract Background Glutathione S‐transferase omega‐1 and 2 have a unique range of enzymatic activities, including the regeneration of ascorbate by their dehydroascorbate reductase activities. Because these enzymes could have a protective role from oxidative damage in the lens, the question of whether the two coding glutathione S‐transferase omega polymorphisms confer the risk of age‐related cataract was addressed. Methods rs4925 (Ala140Asp) of glutathione S‐transferase omega‐1 and rs156697 (Asn142Asp) of glutathione S‐transferase omega‐2 polymorphisms in 100 patients with age‐related cataract and 130 controls were assessed. Results Presence of one mutant GSTO1*Asp or GSTO2*Asp allele did not contribute independently towards the risk of cataract; however, homozygous carriers of GSTO1*Asp/GSTO2*Asp haplotype demonstrated 3.42‐fold enhanced risk of cataract development (95% confidence interval = 0.84–13.93; P = 0.086). When GSTO genotype was analysed in association with smoking or professional exposure to ultraviolet irradiation, carriers of at least one mutant GSTO2*Asp allele had increased risk of cataract development in comparison with individuals with wild‐type GSTO2*Asn/Asn with no history of smoking or ultraviolet exposure (odds ratio = 6.89, 95% confidence interval = 1.81–16.21, P = 0.005; odds ratio = 4.10, 95% confidence interval = 1.23–13.74, P = 0.022, respectively). Regarding the distribution of particular glutathione S‐transferase omega genotype and cataract type, the highest frequency of mutant GSTO2*Asp allele was found in patients with nuclear cataract. Conclusion The results indicate that mutant GSTO2*Asp genotype is associated with increased risk of age‐related cataract in smokers and ultraviolet‐exposed subjects, suggesting a role of inefficient ascorbate regeneration in cataract development.